Magnifier: poems - Krieg, Brandon, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2019)
A magnifier praises what's larger and a magnifier concentrates poisons. Brandon Krieg's Magnifier is a book of spirits invoked by destroyers. It trains its gaze on the deep dependencies we are urged daily to hide from ourselves and interrogates the ways we insulate ourselves from the environmental and social degradations we perpetrate, often at many removes. Magnifier is a book of systems of our collective making that have taken on a life of their own, which we pretend to control. It is a book mourning Romanticism's naiveté, even as it cannot help but engage in a search for meanings not commercial or ideological in the more-than-human world. And yet, the poems in Magnifier refuse to let slip from their focus the human everywhere, or to retreat into a mystifying "wilderness." If a maple seed is to astonish, it must do so in the neighborhood of a reactor. Formally various, balanced on the edge of order and chaos, the poems in Magnifier cry out for "something more" from the "nothing but" even as they zero in on the damage we have done--provided by publisher.
Winner of the Colorado Prize for Poetry.
Keywords: American poetry -- 21st century